How can architectural form follow ecological function? Mixed methods research with practitioners of architecture and landscape architecture to study their professional insights into perceptions of informal wild spaces, and to explore how biodiversity in general is considered within the design and development process in Ireland. - Nulty, Fiona (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2024)
A major factor in global biodiversity loss is land use change. Several processes influence this, including the expansion of the built environment through development. Consequently, there is a need for development projects to prioritise positive outcomes for biodiversity throughout the entire process. Furthermore, wild spaces are shown to be integral to the preservation of ecology in our urban areas; offering refuges for wildlife and diverse, resilient vegetation. This study explores the intersection of these topics, working with practitioners of architecture and landscape architecture to explore how biodiversity is considered within development and to understand the key factors influencing design and project outcomes. This study also seeks to provide practical recommendations to improve the integration of biodiversity measures into our development systems. Using mixed methods research to gain various insights from practitioners working within the system, themes of context, perceptions, values, connection, policy, knowledge, education, roles, responsibilities, and the project process are explored. The findings suggest that the current process of development does not prioritise biodiversity due to outdated policy systems, and an approach which values mitigation over optimisation. Furthermore, there is a need for targeted education and the collation of practical information to assist practitioners in integrating positive biodiversity measures early in the design process. Finally, the research indicates that increasing legibility, facilitating access, and promoting engagement with nature could positively influence societal perceptions of informal urban wild spaces.
APPROVED
Keywords: informal wild spaces; urban biodiversity; architecture; landscape architecture; design; development; planning; environmental policy; urban novel ecosystems